Observation of Scleractinian juveniles' composition, distribution, and density in shallow waters of Kondang Merak Beach, Southern Malang, East Java, Indonesia - ROSDIANTO ROSDIANTO; OKTIYAS MUZAKY LUTHFI; ANWAN RAHMAT ARDIANSYAH; M. AZUREA BAHRI LUTHFI; ANDIK ISDIANTO; DESY SETYONINGRUM; ARIEF SETYANTO; LISA NUR HIDAYAH; AULIA LANUDIA FATHAH; BERLANIA MAHARDIKA PUTRI; NOVAR KURNIA WARDANA; SUPRIYADI SUPRIYADI (Society for Indonesian Biodiversity, 2024)
Abstract. Rosdianto, Luthfi OM, Ardiansyah AR, Luthfi MAB, Isdianto A, Setyoningrum D, Setyanto A, Hidayah LN, Fathah AL, Putri BM, Wardana NK, Supriyadi. 2024. Observation of Scleractinian juveniles' composition, distribution, and density in shallow waters of Kondang Merak Beach, Southern Malang, East Java, Indonesia. Biodiversitas 25: 2663-2668. Kondang Merak Waters, a habitat for various hard corals that grow in flat areas of intertidal reefs, serve as a crucial location for understanding the influence of juvenile corals on the dynamics of coral communities in shallow waters. The research was conducted in 2020 in Kondang Merak, which studied the composition and abundance of young corals on natural substrates on shallow reef flats and reef slopes. Quadrant transects measuring 1x1 m were deliberately placed to observe coral juveniles at two research stations. Quadrant transects are placed along a 100-meter line transect. Visible juvenile corals are counted and identified at the genus or species level. The six types of coral juveniles identified are Favites flexuosa, Goniastrea favulus, Goniastrea aspera, Porites lobata, Montipora digitata and Montipora foliosa. The overall density of juveniles is low, ranging from 0.01-0.08 colonies m-2, with the highest density belonging to F. flexuosa and the lowest belonging to M. foliosa. The six species found showed a clustered distribution pattern, except for two species, namely Goniastrea aspera and M. foliosa, which showed a uniform distribution pattern. Coral juveniles have specific strategies depending on biology and environmental factors. This study revealed the distribution and composition of coral juveniles in intertidal areas as representative of dynamic ecosystems in coastal areas.